Non‐invasive assessment of cutaneous wound healing using fluorescent imaging. Issue 1 (26th July 2014) - Lee, O.; Kim, J.; Park, G.; Kim, M.; Son, S.; Ha, S.; Oh, C.
<x xml:space="preserve">Abstract</x> Background/purpose Optical imaging is a very important technique in the biomedical sciences. The purpose of this study was to develop an in vivo optical system for fluorescent imaging and molecular imaging applications using quantum dots (QDs). Methods The in vivo optical system was composed of modular parts, including a light source, light guide, excitation filter wheel, excitation filters, emission filter wheel, emission filters, liquid crystal tunable filter (LCTF), macro lens, dark chamber, and a cooled charged‐coupled device (CCD) camera for recording images. Filters were selected based on the excitation and absorption spectra of QDs to allow spectral separation and optimization of the acquired image. In contrast with conventional systems, our system allows selection of the emission bandwidth. Results The system was tested in an in vivo study using a wound‐healing model in nude mice. The healing process was examined after injection of fibroblasts and keratinocytes labeled with two different sets of QDs. The different QD probes were readily detected and distinguished using our system. Conclusion An in vivo optical system is a very useful tool for the detection of genes, proteins, and small‐molecule drugs inside living animals, and this imaging modality can also be adopted for real‐time visualization of cancer cell metastasis in live animals.